An Analysis of the Impact of Digital Marketing and Social Media on the Growth of the Islamic Banking Industry in the Modern Era - Gustin Rianita; Muhammad Iqbal Fasa (Denasya Smart Publisher, 2025)
The advancement of digital technology has driven Islamic banking to leverage digital marketing and social media to expand its market reach and enhance competitiveness. This study aims to analyze the impact of digital marketing on the growth of the Islamic banking industry in the modern era. Using a qualitative approach with descriptive analysis, this research examines various literature related to digital marketing and social media in Islamic banking. The findings indicate that digital marketing strategies through platforms such as Instagram, YouTube, and Facebook can increase the number of customers, strengthen the image of Islamic banks, and be more cost-efficient in promotions. However, challenges such as data security, compliance with Sharia principles, and digital literacy gaps still need to be addressed. Therefore, Islamic banks must implement effective digital marketing strategies that align with Sharia principles to maintain customer trust.